FUNGSI PENGAWASAN DPRD SEBAGAI TINDAK LANJUT HASIL PEMERIKSAAN LAPORAN KEUANGAN BADAN PEMERIKSA KEUANGAN DI PROVINSI BENGKULU: DPRD's Supervision Function as a Follow-up to the Audit Results of the Financial Audit Agency's Financial Reports in Bengkulu Province - Avitama, Muhammad Fiqry; Edwar, Ferry (AMICUS CURIAE, 2024)
Indonesia is a unitary state governed by the Constitution of 1945, and one of its key priorities is to integrate regional autonomy into central administration. This research aims to evaluate the supervisory role of the Financial Audit Agency of the Regional Government of Bengkulu Province in 2021 during the new normal period of financial report audit results follow-up, by the provisions of Law No. 23 of 2014 concerning the Regional Government. The type of research used is normative, and the nature of the research is descriptive. The data used are secondary, qualitative analysis, and deductive methods of conclusions. The findings of the study indicate that the Bengkulu Province DPRD's oversight of the Bengkulu Province Regional Government's performance did not entirely correspond with expectations or the circumstances of the pandemic at the time. Notwithstanding explicit legislative mandates, the DPRD encountered both internal and external obstacles that compromised the efficacy of its supervision. The challenges that arose included issues with member coordination, competing interests between factions and limited participation in the development of regulations specifically about COVID-19. Although the DPRD of Pekanbaru City complied with the majority of the provisions outlined in Law Number 23 of 2014, there were still certain aspects of the financial audit results follow-up that were not optimal due to limitations in the available information.